Transcriptome of the inner circular smooth muscle of the developing mouse intestine: Evidence for regulation of visceral smooth muscle genes by the hedgehog target gene, cJun. Issue 5 (17th March 2016) - Gurdziel, Katherine; Vogt, Kyle R.; Walton, Katherine D.; Schneider, Gary K.; Gumucio, Deborah L.
Abstract : Background: Digestion is facilitated by coordinated contractions of the intestinal muscularis externa, a bilayered smooth muscle structure that is composed of inner circular muscles (ICM) and outer longitudinal muscles (OLM). We performed transcriptome analysis of intestinal mesenchyme tissue at E14.5, when the ICM, but not the OLM, is present, to investigate the transcriptional program of the ICM.Results: We identified 3967 genes enriched in E14.5 intestinal mesenchyme. The gene expression profiles were clustered and annotated to known muscle genes, identifying a muscle‐enriched subcluster. Using publically available in situ data, 127 genes were verified as expressed in ICM. Examination of the promoter and regulatory regions for these co‐expressed genes revealed enrichment for cJUN transcription factor binding sites, and cJUN protein was enriched in ICM. cJUN ChIP‐seq, performed at E14.5, revealed that cJUN regulatory regions contain characteristics of muscle enhancers. Finally, we show that cJun is a target of Hedgehog (Hh), a signaling pathway known to be important in smooth muscle development, and identify a cJun genomic enhancer that is responsive to Hh.Conclusions: This work provides the first transcriptional catalog for the developing ICM and suggests that cJun regulates gene expression in the ICM downstream of Hh signaling. Developmental Dynamics 245:614–626, 2016 . © 2016 Wiley Periodicals, Inc. Key findings: Intestinal visceral smooth muscle genes inner circular muscle Hedgehog signaling cJun.